Using Weighted-Robustness Analysis in Strategy Selection (Case Study: Saipa Automotive Research and Innovation Center) - Ali Sorourkhah; Adel Azar; Saman Babaie-Kafaki; Mohsen Shafiei Nik Abadi (مدیریت صنعتی, 2017)
Choosing the best option (strategy) in a decision-making process has always brought about some challenges. In this research, while reviewing some of the widely used and well-known methods in this field, a matrix-weighted approach will be presented to address the weaknesses of the existing methods. This approach allows simultaneous attention to the dimensions of the complexity and uncertainty of the problem and is implemented in a collaborative situation. In addition, three important weaknesses of the classic robustness analysis method concerning the examination of a small number of scenarios, the uncertainty about the outcome of some decisions in terms of different criteria in the form of some scenarios and the lack of attention to the weight and importance of the factors shaping future scenarios, are considered in the above approach. In the end, we will apply the proposed approach in a case study for Saipa automotive research and innovation center and will describe the results afterwards.